Palatal rugae assessment using plaster model and dental scan: a cross-sectional comparative analysis - Laura Roselli; Federica Mele; Carmela Suriano; Valeria Santoro; Roberto Catanesi; Massimo Petruzzi (Frontiers in Oral Health)
ObjectiveDue to their consistent and individualistic patterns, palatal rugae (PR) are used in forensic dentistry as an ancillary method for personal identification. This study aimed to compare the impression of the PR obtained with the classic alginate impression and casting of the plaster model with the impression of the palate made with an intraoral scanner. Both impressions were compared with each other and with the photograph of the palatal rugae.Materials and methodsIn this study, 19 patients (6 men, 13 women; mean age 28.6 years) were selected. Two different impressions were taken from the maxillae of the participants: a conventional impression using alginate impression material, and an optical impression using an intraoral scanner. The impressions obtained were compared with each other and with the photograph of the palatine rugae of each enrolled patient, using FaceComp™ software. The parameters assessed included absolute and relative distances, perimeters, areas, shape factors, and moments. The statistical analysis was conducted using Python 3.9.ResultsThe data from digital and plaster models were comparable across all six parameters used by the software. The coefficients of correlation and determination were strong to very strong for all six parameters assessed, with no statistically significant differences detected between the two methods of palatal rugae impression.ConclusionBoth digital and traditional methods were equally reliable in capturing palatal rugae patterns. The use of FaceComp™ software facilitated accurate comparison and personal identification through the alignment of the preidentified landmarks. Further studies are required to enhance the speed and precision of image acquisition and comparison for broader application in personal identification.